SOSIAL-EKONOMI MASYARAKAT PENDUKUNG SENI CADAS LEANG SUMPANG BITA, KABUPATEN PANGKAJENE KEPULAUAN, SULAWESI SELATAN - Adrian Pasaribu, Yosua (Balai Arkeologi Sumatera Selatan, 2016)
Smith, Adam. 1776. An Inquiry into the Nature and Causes of the Wealth of Nations. London.W. Strahan dan T. CadellWhitley, David S.; Joseph M. Simon; dan Ronald I. Dorn. 1998.Rock Art Studies at CA-SBR-2347, The Paradise Bird Site, Fort Irwin N.T.C; San Bernandino County, California.Report on filem Archaeological Information Center. San Bernandino County Museum.Whitley, David S. 2005. Introduction to Rock Art Research. California. Left Coast Press. Inc.Permana, R. Cecep Eka. 2008.Bentuk-Bentuk Gambar Telapak Tangan pada Gua-Gua Prasejarah di Kabupaten Pangkajene Kepulauan, Sulawesi Selatan. dipublikasikan online di http://melayuonline.com/ind/article/read/798/bentuk-gambar-telapak-tangan-pada-gua-gua-prasejarah-di-kabupaten-pangkajene-kepulauan-sulawesi-selatan.Sauvet, Georges; Robert Layton; Tilman Lenssen-Erz; Paul Taon; dan Andre Wlodarczyk. 2009. Thinking with Animals in Upper Palaeolithic Rock Art; Cambridge Archaeological Journal 19:3, McDonald Institute for Archaeological Research.Sveiby, Karl-Erik. 2009.The First Leadership? Shared Leadership in Indigenous Hunter-Gatherer Bands. Draft Paper for Book Chapter on Indigenous Leadership to be published in 2009.Balai Pelestarian Peninggalan Purbakala Makassar. 2010.Usulan Penetapan Kawasan Gua-gua Prasejarah Maros-Pangkep sebagai Kawasan Strategis Nasional. Direktorat Peninggalan Purbakala; Kementerian Kebudayaan dan Pariwisata; Jakarta (tidak diterbitkan).Balai Pelestarian Peninggalan Purbakala Makassar. 2011.Zonasi Gua-Gua Prasejarah Kabupaten Pangkep 2011. Makassar. Kementerian Kebudayaan dan Pariwisata.McKie. 2014.Cave art and harpoon tips show African roots of our creative genius; The discovery of wall paintings in Indonesian caves suggests that the human ability to express ourselves began before we trekked out of Africa.diaksesonline pada tanggal 11 Oktober 2014 dihttp://www.theguardian.com/science/2014/oct/11/cave-paintings-indonesia-african-roots.Svissero, Serge dan Clem Tisdell. 2014. Hunter-Gatherer Societies: Their Diversity and Evolutionary Procceses dalam Economics, Ecology, and The Environment; University of Queensland.Vergano, Dan. 2014.Cave Paintings in Indonesia Redraw Picture of Earliest Art: The dating discovery recasts ancient cave art as a continent-spanning human practice.diterbitkan pada tanggal 8 Oktober 2014 di http://news.nationalgeographic.com/news/2014/10/141008-cave-art-sulawesi-hand-science/.